Costs and benefits of a leaf beetle Integrated Pest Management (IPM) program II. Cost-benefit analysis. Issue 1 (2nd January 2018) - Cameron, N.; Wardlaw, T.; Venn, T.; Carnegie, A.; Lawson, S.
ABSTRACT: Forest health and biosecurity programs rarely capture sufficient data to enable thorough cost-benefit analyses to be done. One notable exception has been Forestry Tasmania's research project to develop and use an Integrated Pest Management (IPM) program for the leaf beetle Paropsisterna bimaculata . For this project we were able to estimate all major costs and benefits in monetary terms for the period 1975–2034, to allow analysis of a 'control' and a 'no control' option across a full rotation. Overall, the 1975–2034 leaf beetle IPM project provided a net positive return at a 5% discount rate. However, the case study was atypical because research commenced nearly three decades before the IPM program was used operationally in the expanding eucalypt plantation estate. For this reason, the year 1990, when research on the precursor of the operational IPM program commenced, was chosen as the default base year for commencing cash-flow analyses. The present value (in AU as at 2015) of the total expenditure between 1990 and 2034 on research to develop the leaf beetle IPM program and on its operational use was 5.4 million, of which nearly 60% was expended on research. The research costs included costs to develop the operational IPM program using conventional insecticides and costs involved in unsuccessful attempts to develop an IPM program using more environmentally friendly control options. When research expenditure was restricted to that needed for developing an IPM program using conventional insecticides, the internal rate of return from the project exceeded 7.5%. Additional timber yields from using the IPM program translated to additional revenues, which resulted in positive cash flows after 2011. The benefit:cost ratio resulting from the operational use of the IPM program (treating research expenditure as sunk costs) was 7.5. The long interval between commencing research, and applying the IPM program operationally once the plantation estate had become established, is not typical of the circumstances relating to future pest threats. Nonetheless, the findings from our study are still relevant to projects involving future pests that may cause similar damage. Another finding of the study was that research needed for future projects to develop an operational pest management program will provide greater benefit if done centrally and the resultant program adopted broadly by as many affected plantation owners as possible.